Novel therapeutic approaches for childhood parkinsonism. (25th February 2016) - Ng, Joanne; Zhen, Juan; Meyer, Esther; Erreger, Kevin; Pope, Simon; Borck, Guntrum; Heales, Simon J H R; Reith, Maarten E A; Rahim, Ahad A; Waddington, Simon N; Kurian, Manju A
Abstract: Background: Dopamine transporter deficiency syndrome (DTDS) is a primary neurotransmitter disorder caused by loss-of-function mutations in SLC6A3, which encodes the dopamine transporter (DAT). The syndrome is characterised by progressive infantile-onset dystonia-parkinsonism with raised dopamine metabolite homovanillic acid in the cerebrospinal fluid. There are no disease modifying therapies for this life-limiting disorder. The aims of this study were to evaluate the clinical disease spectrum and develop a novel gene therapy approach for DTDS. Methods: Patients aged 1–36 years with childhood-onset dystonia-parkinsonism and suggestive neurotransmitter profile had SLC6A3 sequenced. In-vitro functional studies were undertaken for identified missense mutations. We specifically phenotyped DAT knockout (–/–) mice motor behaviour as a model of DTDS and developed a preclinical viral gene therapy construct. We evaluated effects of intracranial delivery of DAT gene therapy in neonatal DAT–/– mice as a proof of concept study. Findings: We identified ten new patients harbouring seven novel missense mutations, and found a novel atypical phenotype of juvenile parkinsonism. In-vitro functional characterisation revealed multifactorial disease mechanisms, including abnormal DAT trafficking, glycosylation, and impaired substrate recognition and uptake function. The DAT–/– mouse clearly recapitulated many features of human disease, including reduced survival, early hyperkinesia with later parkinsonism, raised homovanillic acid concentrations, and neurodegeneration. We have evaluated viral gene therapy approaches to target dopaminergic neurons and subsequently delivered DAT via adeno-associated virus type 9 to neonatal DAT–/– mice, with improved survival rates and motor phenotype. Interpretation: We report an expanding disease spectrum in DTDS, in which the clinical presentation mimics both cerebral palsy and juvenile parkinsonism. Genotype–phenotype correlation is evident, with in-vitro functional studies demonstrating greater residual DAT function in later-onset milder forms of disease. The preclinical study of viral gene therapy in neonatal mice is promising and will facilitate the longer term aim towards clinical translation for this untreatable disorder. Funding: Medical Research Council Clinical Research Training Fellowship, Great Ormond Street Hospital Children's Charity.